Masyarakat dan Problematika Administrasi Wakaf (Upaya Pemberdayaan Produktivitas Aset Wakaf di Desa Sooko, Kabupaten Ponorogo) - Noviana, Lia; Susilawati, Ika; Awaludin, Asep (LP2M of Institute for Research and Community Services - UIN Walisongo, 2021)
Problems related to the misused of waqf assets have been taking their long way since previous decades to this era, as what has happened in Sooko Village, Ponorogo. Of the 31 mosques and prayer rooms that do not yet have a certificate, 11 areas have AIW while the rest of those have not recorded to have a waqf pledge. In addition, the discovery of Nadzir data, which recorded almost all of them have died and the waqf data entered in the Ministry of Religion's web (siwak) only lists the use of objects and addresses globally, which becomes a problem in the management of waqf assets. The method used in this research is Asset Based Community Development (ABCD). The results showed that the majority of waqf conditions in Sooko Village, Ponorogo, were not yet certified, Nadzir's Human Resources also still did not meet the expected standards. Stakeholder efforts in solving waqf problems in Sooko village, Ponorogo, are by organizing nadzir professionalism training in managing waqf assets and mass waqf pledges in Sooko sub-district, Ponorogo.Permasalahan yang berkaitan dengan aset wakaf yang disalahgunakan bukanlah merupakan hal baru, begitu pula yang terjadi di desa Sooko Kabupaten Ponorogo. Dari 31 masjid dan mushola belum memiliki sertifikat (11 bidang sudah AIW selebihnya belum melakukan ikrar wakaf). Selain itu, ditemukannya data Nadzir yang tercatat hampir keseluruhan sudah meninggal dunia serta data wakaf yang diinput dalam siwak web kementerian agama hanya mencantumkan kegunaan objek dan alamat secara global menjadi masalah dalam pengelolaan aset wakaf. Metode yang digunakan dalam penelitian ini adalah Asset Bassed Community Development (ABCD). Hasil penelitian menunjukkan bahwa kondisi wakaf di desa Sooko Kabupaten Ponorogo mayoritas belum tersertifikasi, Sumber Daya Manusia Nadzir juga masih belum memenuhi standar yang diharapkan. Adapun upaya Stakeholder dalam penyelesaian problematika wakaf di desa Sooko Kabupaten Ponorogo ialah dengan menyelenggarakan pelatihan profesionalisme nadzir dalam mengelola asset wakaf serta ikrar wakaf massal se kecamatan Sooko Kabupaten Ponorogo.